Modelo de movilidad sostenible para la implementación de una ciclovía en el centro urbano de la ciudad de Quevedo - Arguello Suárez, Tito André (2021)
The present project "Sustainable mobility model for the implementation of a bicycle lane in the urban center of the city of Quevedo, Ecuador 2021" seeks to promote an alternative of mobility in the city center, which allows to reduce the problems that are generated by the growth of the vehicle fleet, a mobility diagnosis was carried out, the main streets of the city center were analyzed where coordinates of transit points and road characteristics were taken, a two-week capacity was made where traffic was monitored for 8 hours a day Every 15 minutes, in two main streets it was determined that the vehicle with the greatest use is the light vehicle (Automobile) with 61% in each street, the motorcycle is the second vehicle used with 28% and 25% in each of the streets , while cycling only reaches 2%, a survey was applied to determine the citizen perspective regarding the current mobility system and the implementation of a mobile solution It is determined that road safety is a determining factor in potential cyclists, as well as the environmental and health effect that citizens feel by the current transport system, it was determined that road safety is a determining factor for the current transport system, and ArcGIS was used to perform the analysis. multicriteria where values were established for each criterion in the Reclassify tool, elaborating thematic maps that were then weighted in the Weighted Overlay tool, indicating the optimal routes for the bicycle lane, strategies were described in 6 thematic areas in the short, medium and long term according to bibliography of strategies successfully implemented in other cities around the world, in order to promote the use of cycling in the city center and in the Quevedo canton. Keywords: Sustainable mobility; Bike; Bikeway; Mobility diagnosis, Multi-criteria analysis.